1996
DOI: 10.1002/jpln.1996.3581590406
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of active soil carbon and nitrogen pools under intensive cropping in conventional and no tillage

Abstract: Active fractions of soil carbon (C) and nitrogen (N) CM undergo seasonal changes due to environmental and cultural factors, thereby influencing plant N availability and soil organic matter (SOM) conservation. Our objective was to determine the effect of tillage (conventional and none) on the seasonal dynamics of potential C and N mineralization, soil microbial biomass C (SMBC), specific respiratory activity of SMBC (SRAC), and inorganic soil N in a sorghum [SoghurnMerr.] rotation and in a wheet/soybean double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In particular, Gagliardi and Karns (2002) employed a higher incubation temperature (25°C, compared with 15°C for the maize cores). Higher temperatures may stimulate plant photosynthetic activity, leading to increased rhizodeposition (Franzluebbers et al. 1996; Pramanik et al.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Gagliardi and Karns (2002) employed a higher incubation temperature (25°C, compared with 15°C for the maize cores). Higher temperatures may stimulate plant photosynthetic activity, leading to increased rhizodeposition (Franzluebbers et al. 1996; Pramanik et al.…”
Section: Discussionmentioning
confidence: 99%
“…These forms of conventional and deep tillage have also been known to increase organic C mineralisation by changing the distribution of SOM in the soil profile. Franzluebbers et al. (1996) observed that mineralisation increased under conventional tillage compared with no‐till.…”
Section: Saline and Sodic Effects On Soil Organic Carbon Dynamicsmentioning
confidence: 95%
“…They are all valuable indicators to soil quality and health. (Franzluebbers et al 2000;Franzluebbers, Hons, and Zuberer 1996) The SIR-SMBC procedure presented in this study, however, is the only one that can be conveniently determined in real time and under field conditions. The correlations between the SIR-SMBC and the soil organic matter (Figure 4, r 2 = 0.548) and between SIR-SMBC and the total soil nitrogen ( Figure 5, r 2 = 0.387) are also significant but to a lesser extent as compared with the correlation between the SIR-SMBC and the 10-day incubation mineralized C. These lesser correlations are expected because SMBC is not only a function of the quantity but also the quality of the organic matter and nitrogen.…”
Section: Sir-smbc and The 10-day Incubation Mineralized Carbonmentioning
confidence: 99%
“…It was found that the CO 2 flush after rewetting dried soils could be an indicator of soil microbial mineralization capability (Marumoto, Anderson, and Domsch 1982;Sorensen 1974;Sparling et al 1995). The three-day CO 2 flush after rewetting dried soils was also found to be correlated to soil microbial biomass, active soil carbon pool, and net nitrogen mineralization (Franzluebbers and Haney 2018;Franzluebbers et al 2000;Franzluebbers, Hons, and Zuberer 1996). Soil respiration measurements were usually determined by the exhaustive CO 2 absorption (by alkaline) approach such as alkaline trap-titration (Keeney 1982), Solvita (Haney, Brinton, and Evans 2008) or Draeger tube (Soil Quality Institute 1999) methods.…”
Section: Introductionmentioning
confidence: 96%